Regulation of lipid peroxidation and ferroptosis in diverse species - Conrad, Marcus; Kagan, Valerian E; Bayir, Hülya; Pagnussat, Gabriela C; Head, Brian; Traber, Maret G; Stockwell, Brent R (Genes & development, 2018)
Lipid peroxidation is the process by which oxygen combines with lipids to generate lipid hydroperoxides via intermediate formation of peroxyl radicals. Vitamin E and coenzyme Q react with peroxyl radicals to yield peroxides, and then these oxidized lipid species can be detoxified by glutathione and glutathione peroxidase 4 (GPX4) and other components of the cellular antioxidant defense network. Ferroptosis is a form of regulated nonapoptotic cell death involving overwhelming iron-dependent lipid peroxidation. Here, we review the functions and regulation of lipid peroxidation, ferroptosis, and the antioxidant network in diverse species, including humans, other mammals and vertebrates, plants, invertebrates, yeast, bacteria, and archaea. We also discuss the potential evolutionary roles of lipid peroxidation and ferroptosis.